2022
DOI: 10.32996/jpbs.2022.2.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Smartphone Addiction, Personality Traits, Achievement Motivation on Problem-solving Ability of University Students

Abstract: This study aimed to analyze the relations between smartphone addiction, personality traits, achievement motivation and problem-solving ability and explore the influence of smartphone addiction, personality traits, achievement motivation on university students' problem-solving ability. 682 students (male = 227, female = 455) from a Chinese public university participated in the research voluntarily. Data were collected by the short-version of the smartphone addiction scale, the ten-item personality inventory, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Besides this, a number of authors report a signi cant relationship between smartphone / internet addiction and certain personality traits and often accent the role of neuroticism. Examples can be found in studies by Xie Ran (2022), Sun and Wilkinson (2020), or Kuem and Rya (2022) [20][21][22][23][24][25][26]. Some authors explored the relationship between technology addiction and outcomes relevant for an academic environment.…”
Section: Review Of Current Evidence On This Study Topicmentioning
confidence: 99%
“…Besides this, a number of authors report a signi cant relationship between smartphone / internet addiction and certain personality traits and often accent the role of neuroticism. Examples can be found in studies by Xie Ran (2022), Sun and Wilkinson (2020), or Kuem and Rya (2022) [20][21][22][23][24][25][26]. Some authors explored the relationship between technology addiction and outcomes relevant for an academic environment.…”
Section: Review Of Current Evidence On This Study Topicmentioning
confidence: 99%
“…Similarly, Serdar, Demirel, & Demirel (2022) found that university students when face boredom, they become dissatisfied and ultimately start using the smart phones immensely which results in Smartphone addiction. Studies show that smart phone addiction has a profound impact on individual's personality traits and problem-solving ability among university students (Ran, 2022). Studies also indicate that it also negatively affects university students' sleep quality and perceived stress (Sanusi, Al-Batayneh, Khader & Saddki, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This ability is essential for students to learn geography [13]. The problems contained in geography are not appropriately identified by students [14].Therefore, the indicators contained in the PSA will assist students in integrating their knowledge to identify problems and make clear problem solutions [15]. In addition, through PSA, students can use their thinking and reasoning abilities.…”
Section: Introductionmentioning
confidence: 99%